The Impact of Entrepreneurial Orientation and Collaborative Networks on Creative Industries Performance - Mulyana, Mulyana; Sutapa, Sutapa (JDM (Jurnal Dinamika Manajemen), 2016)
Creative industries significantly contribute to Indonesia economic development. There are many problems faced especially in improving innovation capabilities and competitive advantages. This study proposes to examine the effect of collaborative networks and entrepreneurial orientation to innovation capabilities, competitivee advantage and performance. Some creative industries located at several cities in the Central Java Province. Sampling methods used in this study is purposive sampling and data is analyzed by the multiple linier regressions. The result of this study shows that entrepreneurial orientation significantly affects both the innovation capability and performance. Collaborative networks significantly affects both the innovation capability and competitive advantage. Furthermore, the result shows that entrepreneurial orientation, innovation capability and competitive advantage significantly affect the performance. Nevertheless, it shows that collaborative networks do not significantly affect the performance.